Real-Life Experience of Regorafenib in Patients With Advanced Hepatocellular Carcinoma - Hou, Jing-Yu; Xiao, Ya-ting; Huang, Jing-Bo; Jiang, Xin-Hua; Jiang, Kai; Li, Xun; Xu, Li; Chen, Min-Shan (Frontiers in Pharmacology, 2022)
Background:The RESORCE trial reported that regorafenib was effective as the second-line treatment for patients with hepatocellular carcinoma (HCC) after progression on sorafenib. Real-world data are needed to assess clinical outcomes and adverse events in the setting of daily practice. Objective:We aimed to evaluate the efficacy and safety of regorafenib after disease progression with sorafenib in Chinese patients with advanced HCC. Patients and methods: A total of 41 patients with advanced HCC who did not respond to sorafenib and followed a regorafenib regimen were enrolled in this retrospective study. Overall survival (OS), progression-free survival (PFS), radiological responses, and adverse events (AEs) were evaluated. Survival curves were compared by using the log-rank test and constructed with the Kaplan–Meier method. Results: The median PFS with regorafenib was 6.6 months (range: 5.0-8.2 months), and the median OS was not reached. The 1-year OS rate of regorafenib was 66.4%. The median OS of sequential sorafenib-regorafenib treatment was 35.3 months (95% CI: 24.3-46.3), and the 2-year OS rate of sequential sorafenib-regorafenib treatment was 74.4%. The most frequent AEs during regorafenib treatment were elevated aspartate aminotransferase (17/41 patients [41.5%]), elevated alanine aminotransferase (16/41 patients [39%]) and hand-foot syndrome (14/41 patients [34.1%]). Conclusions: Regorafenib seems safe and clinically efficacious in patients with advanced HCC who progressed on first-line sorafenib.